Induction of Ocular Surface Inflammation and Collection of Involved Tissues - Singh, Jeeshan; Shan, Xiaomei; Mahajan, Aparna; Herrmann, Martin; Schauer, Christine; Knopf, Jasmin; Munoz Becerra, Luis (Journal of Visualized Experiments, 2022)
Ocular surface diseases include a range of disorders that disturb the functions and structures of the cornea, conjunctiva, and the associated ocular surface gland network. Meibomian glands (MG) secrete lipids that create a covering layer that prevents the evaporation of the aqueous part of the tear film. Neutrophils and extracellular DNA traps populate MG and the ocular surface in a mouse model of allergic eye disease. Aggregated neutrophil extracellular traps (aggNETs) formulate a mesh-like matrix composed of extracellular chromatin that occludes MG outlets and conditions MG dysfunction. Here, a method for inducing ocular surface inflammation and MG dysfunction is presented. The procedures for collecting organs related to the ocular surface, such as the cornea, conjunctiva, and eyelids, are described in detail. Using established techniques for processing each organ, the major morphological and histopathological features of MG dysfunction are also shown. Ocular exudates offer the opportunity to assess the inflammatory state of the ocular surface. These procedures enable the investigation of topical and systemic anti-inflammatory interventions at the preclinical level.
CRIS-Team Scopus Importer:2022-09-02